Proliferation of paradigmatic ruptures: the case of evidence-based medicine - Vasconcellos-Silva, Paulo Roberto; Castiel, Luis David (Revista de Saúde Pública, 2005)
The present study describes the phenomenon of paradigmatic ruptures proliferation in the biomedical literature. The current distortion is discussed, which has conferred in the last decades an opposite meaning to the term originally proposed by Thomas Khun. In most part, it is realized that pseudo-ruptures refer to technical details associated to specific contexts. It is pointed out the case of evidence- based medicine (EBM), proclaimed as one of these paradigmatic ruptures, but which essentially corroborates old concepts. Some conceptual errors are stressed as well as attempts to apply EBM assumptions to phenomena associated to subjectivity and social dynamics and other particular study subjects of social sciences. Twelve inconclusive meta-analyses are described to exemplify the paradoxes emerging from this approach. The criticism to some EBM features is summarized through the effects of epistemological bafflement, producing conceptual inaccuracies of the term; the defensive effect to which other disciplines are induced for not being adequate to such rationality; and the tendency of universal understanding of phenomena through the perspective of randomized double-blind studies.